Spatially-selective optical pumping cooling and two-isotope collision-assisted Zeeman cooling - Wilson, Rebekah Ferrier, author; Roberts, Jacob, advisor; Krueger, David, committee member; Lundeen, Stephen, committee member; Marconi, Mario, committee member (Colorado State University. Libraries, 2014)
In this thesis I describe two non-evaporative cooling schemes for cooling Rb atoms. The first is a Sisyphus-like ultracold gas cooling scheme called Spatially-selecTive Optical Pumping (STOP) cooling. In principle, STOP cooling has wide applicability to both atoms and molecules. STOP cooling works by exploiting the fact that atoms or molecules in a confining potential can be optically pumped out of an otherwise dark state in a spatially-selective way. Selecting atoms or molecules for optical pumping out of a dark state in a region of high potential energy and then waiting a fixed time after the optical pumping allows for the creation of a group of high kinetic energy atoms or molecules moving in a known direction. These can then be slowed using external fields (such as the scattering force from a resonant laser beam) and optically pumped back into the dark state, cooling the gas and closing the cooling cycle. I present theoretical modeling of the STOP cooling technique, including predictions of achievable cooling rates. I have conducted an experimental study of the cooling technique for a single cooling cycle, observing one dimensional cooling rates in excess of 100 micro-K per second in an ultracold gas of 87Rb atoms. I will also comment on the prospects for improving the cooling performance beyond that presented in this work. The second cooling scheme I investigated is called Two-Isotope Collision Assisted Zeeman (2-CAZ) cooling. Through a combination of spin-exchange collisions in a magnetic field and optical pumping, it is possible to cool a gas of atoms without requiring the loss of atoms from the gas. I investigated 2-CAZ cooling using 85Rb and 87Rb. I was able to experimentally confirm that the measured 2-CAZ cooling rate agreed with a cooling rate predicted though a simple analytic model. As part of the measured cooling rate, I quantitatively characterized the heating rates associated with our actual implementation of this cooling technique and found hyperfine-changing collisions to be a significant limitation for the 85/87Rb gas mixture. Possible improvements to this experiment will be discussed as well as the prospects for improved cooling performance using an atom without hyperfine structure as the optically pumped atom.
Keywords: spatially-selective; sisyphus-like; ultracold; collision assisted Zeeman; non-evaporative cooling